Daily and event‐driven pre‐exposure prophylaxis for men who have sex with men in Belgium: results of a prospective cohort measuring adherence, sexual behaviour and STI incidence. Issue 10 (30th October 2019) - Vuylsteke, Bea; Reyniers, Thijs; De Baetselier, Irith; Nöstlinger, Christiana; Crucitti, Tania; Buyze, Jozefien; Kenyon, Chris; Wouters, Kristien; Laga, Marie
Abstract: Introduction: Pre‐Exposure Prophylaxis (PrEP) is highly effective in reducing the risk for HIV infection among men who have sex with men (MSM) and may have an important impact in slowing down the HIV epidemic. Concerns remain however about low adherence, increased risk behaviour and reduced condom use when using PrEP. The aim of this study was to assess these factors prospectively among MSM using daily and event‐driven PrEP in Belgium. Methods: An open‐label prospective cohort study was conducted from October 2017 to May 2018 at the Institute of Tropical Medicine, in Antwerp, Belgium. At enrolment, MSM at high risk for HIV chose between daily or event‐driven PrEP. They were allowed to switch regimens or stop taking PrEP at each of their tri‐monthly visits. Data were collected on an electronic case report form, web‐based diary and self‐administered questionnaire. Screening for HIV and other Sexually Transmitted Infections (STIs) was also performed. Results: Two hundred MSM were followed up for a total duration of 318 person‐years. At month 18, 75.4% of the participants were on daily and 24.6% were on event‐driven PrEP. The mean proportion of covered sex acts by PrEP for the complete follow‐up period was 91.5% for all participants, 96.5% for daily and 67.0% for event‐driven PrEP use. The number of casual and anonymous sex partners was significantly higher for daily users, as compared with event‐driven users, but did not change over time. In contrast, the mean proportion of condomless receptive anal intercourse with casual and anonymous partners increased significantly during follow‐up, for both daily and event‐driven use ( p < 0.0001 for all 4 trends). No new HIV infection was diagnosed during follow‐up. The incidence of bacterial STIs was 75.4 per 100 person‐years (95% CI 63.8 to 89.1). We did not detect a significant change in N. gonorrhoeae / C. trachomatis incidence over time. The incidence of hepatitis C was 2.9 per 100 person‐years. Conclusions: PrEP is an effective and well adopted HIV prevention tool for MSM in Belgium. Participants adapted daily and event‐driven regimens to their own needs and were able to adapt their PrEP adherence to risk exposure.